HBR's 10 must reads for CEOs (HBR's 10 must reads (Series), 2019)
As CEO, you set the tone for your organization. You establish priorities, anticipate and address challenges, champion and lead change efforts, set people up for success, and manage risk. You look at issues and trends to see how they'll affect your company internally, but also externally--in the larger context of your industry, your country, and your company's place in the global marketplace. You maintain a long-term view while simultaneously paying attention to short-term concerns. And though you may have a great senior executive team and a top-flight board, ultimately the responsibility rests on your shoulders.--